Evaluation of Dot-ELISA Method Using Excretory-Secretary Antigens of Fasciola hepatica in Laboratory Diagnosis of Human Fasciolosis - MB Rokni (Iranian Journal of Parasitology, 2006)
Fasciolosis diagnosis, due to low sensitivity of coprological diagnostic method has been challenging for a long period. In this study, Dot-ELISA, one of the simplest and the most sensitive tests in this regard, was evaluated using excretory-secretory antigens of Fasciola hepatica to diagnose human fasciolosis Three groups consisting of patients infected with fasciolosis (n= 95), patients with other parasitic diseases (n= 37) and healthy individuals (n= 40), were implicated in the test. All collected sera were tested by Dot-ELISA using excretory-secretory antigens. Optimal criteria were detected as 1.5 µg of antigen per dot, serum dilution of 1:320, and anti human IgG conjugate dilution of 1:500. The sensitivity, specificity, positive and negative predictive values were 96.8%, 96.1%, 96.8% and 96.1%, respectively. In conclusion, Dot-ELISA using excretory-secretory antigens could be regarded as a cheap, rapid, antigen and serum conservative diagnostic method in diagnosing fasciolosis.